Bismuth oxygen methacrylic acid hybrid nanocluster with bamboo joint-like structure as well as preparation method and application of bismuth oxygen methacrylic acid hybrid nanocluster
Bismuth oxygen methacrylic hybrid nanoclusters with bamboo-like structures were prepared by a one-step reaction, and their biocompatibility was improved through polymer modification, which solved the problem of difficulty in preparing and structural control of bismuth oxygen nanoclusters in the prior art, and achieved efficient tumor cell killing effect in radiotherapy.
Patent Information
- Application Number
- CN202510109711.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The prior art is difficult to effectively prepare and control the structure of bismuth oxygen nanoclusters, especially at the nanoscale, and its application in radiation therapy has not been fully explored.
By a one-step method, bismuth-oxymethacrylic hybrid nanoclusters with bamboo-like structures are prepared by reacting bismuth-containing compounds and sodium methacrylate at a specific temperature, and their biocompatibility is improved through polymer modification.
The stable preparation and structural regulation of bismuth oxygen nanoclusters were achieved. Nanoclusters with bamboo-like structures showed toxicity in bladder cancer cells and effectively inhibited the proliferation of bladder cancer cells under X-ray irradiation.
Smart Images

Figure CN119874508A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical material preparation, and in particular to a bismuth oxygen methacrylate hybrid nanocluster with a bamboo-like structure, and a preparation method and application thereof. Background Art
[0002] Tumors remain an important threat to human health. Radiotherapy is one of the important treatment measures in the clinical field. More than 50% of cancer patients will use radiotherapy. However, due to the low absorption and utilization rate of cells to X-rays, the therapeutic effect of radiotherapy alone is not obvious, and high radiation doses are often required, which will inevitably cause damage to normal human tissues. The use of nanomaterials with good biocompatibility as radiotherapy sensitizers can enhance the X-ray utilization effect in the lesion area and enhance the tumor cell killing effect through the interaction between the material and X-rays, which is expected to further reduce the total X-ray radiation dose while avoiding excessive radiation side effects to surrounding normal tissues. Therefore, the development of nanomaterials with high X-ray utilization is an important direction to improve the field of tumor radiotherapy.
[0003] Bismuth is the heaviest element among the non-radioactive elements, so it has a high absorption and attenuation coefficient for X-rays. Its K-edge absorption energy is as high as 90.5 keV, and it is also called the "green element". As early as the last century, bismuth-containing compounds were used to treat gastrointestinal diseases and were reported to have good therapeutic effects and biosafety. Therefore, in recent years, bismuth nanomaterials have been widely used as radiosensitizers and CT contrast agents, showing great potential. However, the above materials focus on binary or ternary compounds with determined molecular structures, lack functional exploration of other bismuth-based materials, and are not enough to reveal the important properties of bismuth-based materials in radiotherapy. In addition, the above materials often introduce other elements that the human body does not have, which is bound to impose certain restrictions on the application of the materials. By studying the physiological functions of existing bismuth-containing drugs, it can be found that the bismuth oxygen structure is the main component. Therefore, the exploration of new bismuth-based materials around the bismuth oxygen structure is an important strategy for the development of new bismuth-based contrast agents. However, only some of the work involves the construction of micron-scale cluster structures, and the preparation and application research of controllable nanoscale bismuth oxygen clusters has not been reported.
[0004] Therefore, technicians in this field have been committed to developing a bismuth-oxygen nanocluster with a unique structure, which can be used as a radiotherapy sensitizer to kill tumor cells more effectively. By simulating clinical active ingredients, exploring the construction method, structure and performance regulation of bismuth-oxygen nanoclusters, and revealing more characteristics of bismuth-based nanomaterials in radiotherapy through bladder cancer models, it is of great significance and has broad application prospects. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a bismuth oxygen methacrylate hybrid nanocluster with a bamboo-like structure and a preparation method and application thereof, so as to solve the current problems that inorganic-organic hybrid materials are difficult to prepare and the assembly structure is difficult to control, and the construction of bismuth oxygen clusters composited with methacrylate monomers is realized in a one-step method, which has a bamboo-like nanomorphology and a bamboo-like structure. The nanocluster exhibits obvious toxicity after being internalized by bladder cancer cells, and achieves efficient inhibition of bladder cancer cell proliferation under X-ray irradiation. The present invention reports for the first time a bismuth oxygen methacrylate hybrid nanocluster with a bamboo-like structure, and explores the regulation mode of the nanostructure in terms of mechanism, while providing a potential nanoformulation for the treatment of bladder cancer, with extremely high benefits in nanomaterial construction and clinical diagnosis and treatment.
[0006] The technical solution provided by the present invention is as follows: <First aspect> A method for preparing bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure comprises the following steps: S1, dissolving a bismuth-containing compound in an organic solvent at a certain temperature to form a bismuth-containing organic solution; S2. Adding sodium methacrylate to the bismuth-containing organic solution and reacting it at a certain temperature for a period of time; collecting the reaction product to obtain bismuth-oxygen organic hybrid nanoclusters with a bamboo-like structure.
[0007] In step S1, the bismuth-containing compound includes one or more of bismuth nitrate, bismuth chloride, and bismuth acetate.
[0008] Furthermore, the bismuth-containing compound includes bismuth nitrate. Preferably, the bismuth nitrate is hydrated bismuth nitrate. Furthermore, the hydrated bismuth nitrate includes bismuth nitrate pentahydrate.
[0009] In step S1, the concentration of the bismuth-containing compound in the bismuth-containing organic solution is 0.06-0.03 g / mL; And / or, in step S1, the organic solvent includes one or more of dimethyl sulfoxide, tetrahydrofuran, ethyl acetate, diethyl ether, and N,N-dimethylformamide.
[0010] And / or, in step S1, the temperature condition is 70-90 o C.
[0011] The mass ratio of the bismuth-containing compound to sodium methacrylate is 1.5:1-3:1.
[0012] In step S2, the step of collecting the reaction product from the reaction solution is to centrifuge the reaction solution, collect the precipitate, wash, centrifuge and dry to obtain the bismuth-oxygen organic hybrid nanoclusters with a bamboo-like structure.
[0013] In step S2, the reaction temperature is 70-90° C. and the reaction time is 10-12 hours.
[0014] In step S2, centrifugation conditions: 10000-12000 rpm, 5-10 minutes.
[0015] <Second Aspect> The present invention provides a bismuth oxygen methacrylate hybrid nanocluster having a bamboo-like structure prepared by the preparation method as described above.
[0016] <Third Aspect> A preparation method of a polymer-modified bismuth-oxygen-methacrylate hybrid nanocluster with a bamboo-like structure comprises the following steps: dispersing the bismuth-oxygen-methacrylate hybrid nanocluster with a bamboo-like structure in an organic solvent A to form a dispersion A, adding a phospholipid compound solution to the dispersion A and ultrasonicating for a period of time; centrifuging to collect substances deposited at the bottom of a centrifuge tube, washing, and re-dispersing in a solvent B to form a dispersion B; adding a polymer hydrophilic modified substance to the dispersion B, stirring for a period of time, and obtaining a polymer hydrophilic modified bismuth-oxygen organic hybrid nanocluster material with a bamboo-like structure after the solvent evaporates.
[0017] In the dispersion A, the concentration of the bismuth-oxygen organic hybrid nanoclusters having a bamboo-like structure is 10-20 mg / mL.
[0018] The phospholipid compound includes 1,2-dioleoyl-sn-glycero-3-phosphate sodium salt (DOPA).
[0019] The method for preparing the phospholipid compound solution is as follows: dissolving the phospholipid compound in an organic solvent (such as chloroform) to prepare a phospholipid compound solution with a mass concentration of 2-5 mg / mL.
[0020] The polymer hydrophilic modified substance includes one or more of distearoylphosphatidylethanolamine-methoxy polyethylene glycol 5000 (DSPE-mPEG5000), methoxy polyethylene glycol 2000 derivative (mPEG2000), chitosan, and polydopamine.
[0021] The dosage ratio of the bismuth oxygen methacrylate hybrid nanoclusters with bamboo-like structures to the phospholipid compounds is 2:1-10:1.
[0022] In step S3, the mass ratio of the bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure, the phospholipid compound, and the polymer hydrophilic modified substance is 2:1:1-10:1:1.
[0023] The invention discloses a polymer-modified bismuth-oxygen-methacrylic acid hybrid nanocluster material with a bamboo-like structure.
[0024] The bismuth oxygen methacrylate hybrid nanocluster material with a bamboo-like structure has an average length of 80-200 nm and a width of 40-50 nm, and has good dispersibility, and the specific size can be controlled by experimental conditions.
[0025] The nano clusters of the present invention are spontaneously formed in the preparation process and have a bamboo-like structure.
[0026] The nanoclusters are subsequently surface-modified with hydrophilic polymer methoxy polyethylene glycol 2000 derivatives and the like to enhance biocompatibility.
[0027] The bismuth oxygen methacrylate hybrid nanoclusters with bamboo-like structures prepared by the preparation method also fall within the protection scope of the present invention.
[0028] Compared with the prior art, the present invention has the following beneficial effects: 1. First, there is no prior art method for constructing bismuth-oxygen-methacrylic acid hybrid nanoclusters with bamboo-like structures. The method of the present invention first proposes a stable preparation strategy and reveals that the length size of the nanostructure can be adjusted.
[0029] 2. The present invention solves the current problems of difficult preparation of inorganic-organic hybrid materials and difficult control of assembly structures, and realizes the construction of bismuth oxygen clusters composited with methacrylic acid monomers in one step, which has a nano-morphology similar to bamboo and has a bamboo node structure.
[0030] 3. Bismuth element with high responsiveness to X-rays was selected as the matrix material, and sodium methacrylate monomer was used as the structure regulator. Bismuth oxygen methacrylate hybrid nanoclusters with bamboo-like structures were prepared in one step at a suitable temperature and feed ratio concentration. By adjusting the reaction concentration, the morphology of the nanostructure has good reproducibility. After surface modification with hydrophilic polymers, the nanoclusters can be engulfed by bladder cancer cells, showing certain biological toxicity, and the proliferation of bladder cancer cells is further inhibited under X-ray irradiation. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a schematic diagram of the preparation route of the polymer-modified bismuth-oxygen-methacrylic acid hybrid nanoclusters with a bamboo-like structure according to Example 4 of the present invention; Figure 2 is a transmission electron microscope image of the bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure of Example 1; Figure 3 is a transmission electron microscope image of the bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure of Example 2; Figure 4 is a transmission electron microscope image of the bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure of Example 3; Figure 5 is a transmission electron microscope image of the bismuth oxygen methacrylate hybrid nanoclusters of Comparative Example 1; Figure 6 is a transmission electron microscope image of the bismuth oxygen methacrylate hybrid nanoclusters of Comparative Example 2; Figure 7 is a transmission electron microscopy image of the bismuth oxygen methacrylate hybrid nanoclusters of Comparative Example 3; Figure 8 In the performance test example, the cell survival rate of polymer-modified bismuth-oxygen-methacrylate hybrid nanoclusters with bamboo-like structures after being internalized by bladder cancer cells; Fig. 9 In the performance test example, the cell survival rate of polymer-modified bismuth-oxygen-methacrylate hybrid nanoclusters with bamboo-like structures in bladder cancer cells irradiated with X-rays before and after cell endocytosis; DETAILED DESCRIPTION The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0032] Example 1 Dissolve 0.9 g of bismuth nitrate pentahydrate in dimethyl sulfoxide (15 mL) and heat at 80 o C until completely dissolved, then add 0.3 g of sodium methacrylate under stirring and continue the reaction for 12 hours (reaction temperature 80°C). After cooling to room temperature, centrifuge at 10,000 rpm for 5 minutes, wash with dimethyl sulfoxide, water and anhydrous ethanol in turn, and dry in vacuum at 80°C for 1 hour to obtain a white powder.
[0033] like Figure 2 As shown, in this embodiment, bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure were prepared, with a length of about 200 nm and a width of about 50 nm.
[0034] Example 2 Dissolve 0.7 g of bismuth nitrate pentahydrate in dimethyl sulfoxide (15 mL) and heat at 80 oC until completely dissolved, then add 0.3 g of sodium methacrylate under stirring, and continue the reaction for 12 hours (reaction temperature 80°C). After cooling to room temperature, centrifuge at 10,000 rpm for 5 minutes, wash repeatedly (same as Example 1), and vacuum dry at 80°C for 1 hour to obtain a white powder.
[0035] like Figure 3 As shown, in this embodiment, bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure were prepared, with a length of about 280 nm and a width of about 50 nm.
[0036] Example 3 Dissolve 0.5 g of bismuth nitrate pentahydrate in dimethyl sulfoxide (15 mL) and heat at 80 o C until completely dissolved, then add 0.3 g of sodium methacrylate under stirring, and continue the reaction for 12 hours (reaction temperature 80°C). After cooling to room temperature, centrifuge at 10,000 rpm for 5 minutes, wash repeatedly (same as Example 1), and vacuum dry at 80°C for 1 hour to obtain a white powder.
[0037] like Figure 4 As shown, in this embodiment, bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure were prepared, with a length of about 230 nm and a width of about 50 nm.
[0038] Example 4 20 mg of the bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure obtained in Example 1 were weighed and dispersed in 1 mL of chloroform, and mixed with 1 mL of a chloroform solution of 1,2-dioleoyl-sn-glycerol-3-phosphate sodium salt with a concentration of 2 mg / mL under ultrasonic conditions (ultrasonic mixing at a power of 120 w for 20 minutes) to prepare a suspension, and the suspension was centrifuged at 8000 rpm for 5 minutes to collect the material deposited at the bottom of the centrifuge tube, and washed (with dimethyl sulfoxide, water and anhydrous ethanol successively) and then redispersed in 1 mL of chloroform, and then 4 mL of a chloroform solution of distearoylphosphatidylethanolamine-methoxypolyethylene glycol with a concentration of 2 mg / mL was added, and magnetic stirring was performed at 300 rpm for 8 hours. Finally, the chloroform solvent was evaporated to obtain a polymer-modified bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure.
[0039] like Figure 1 As shown, it is a schematic diagram of the preparation route of the polymer-modified bismuth-oxygen-methacrylic acid hybrid nanoclusters with bamboo-like structures in this embodiment.
[0040] Comparative Example 1 Dissolve 0.3 g of bismuth nitrate pentahydrate in dimethyl sulfoxide and heat at 80 oC until completely dissolved, then add 0.3 g of sodium methacrylate under stirring and continue the reaction for 12 hours (reaction temperature 80°C). After cooling to room temperature, centrifuge at 10,000 rpm for 5 minutes, wash repeatedly (same as in Example 1), and vacuum dry at 80°C for 1 hour to obtain a white powder, such as Figure 5 As shown, bismuth oxygen methacrylate hybrid nanoclusters with bamboo-like structures cannot be obtained.
[0041] Comparative Example 2 Dissolve 0.3 g of bismuth nitrate pentahydrate in dimethyl sulfoxide and heat at 60 o C until completely dissolved, then add 0.3 g of sodium methacrylate under stirring conditions and continue the reaction for 12 hours (reaction temperature 60°C). After cooling to room temperature, centrifuge at 10,000 rpm for 5 minutes, wash repeatedly (same as in Example 1), and vacuum dry at 80°C for 1 hour to obtain a white powder, such as Figure 6 As shown, bismuth oxygen methacrylate hybrid nanoclusters with bamboo-like structures cannot be obtained.
[0042] Comparative Example 3 like Figure 7 As shown, 0.3 g of bismuth nitrate pentahydrate was dissolved in dimethyl sulfoxide and heated at 100 o C until completely dissolved, then 0.3 g of sodium methacrylate was added under stirring and the reaction was continued for 12 hours (reaction temperature 100°C). After cooling to room temperature, centrifugation was performed at 10,000 rpm for 5 minutes, and repeated washing (same as in Example 1) was performed, and a white powder was obtained after vacuum drying at 80°C for 1 hour. Bismuth oxygen methacrylate hybrid nanoclusters with bamboo-like structures could not be obtained.
[0043] Performance test case The polymer-modified bismuth-oxygen-methacrylic acid hybrid nanoclusters with bamboo-like structures prepared in Example 4 were incubated at different concentrations (0, 50, 100, 200, 400 μg mL -1 The nanoclusters were dispersed in DMEM medium solution and co-incubated with bladder cancer cells MB49 at a density of 10,000 cells / well on a 96-well plate to test the cell survival rate. From the survival rate data, it can be found that the nanoclusters showed obvious tumor cell killing ability after cell endocytosis (such as Figure 8 ), confirming the anti-tumor value of the bismuth oxygen clusters themselves; after co-incubation with bladder cancer cells MB49 at a concentration of 100 μg / mL, they were irradiated with different doses of X-rays and the cell survival rate was tested. From the survival rate data, it can be found that the nanoclusters showed obvious tumor cell killing ability after cell endocytosis and irradiation (such as Fig. 9 ), confirming the radiosensitizing properties of the bismuth oxygen cluster.
[0044] The present invention discloses a method for preparing bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure. By solving the current problems of difficult preparation of inorganic-organic hybrid materials and difficult control of assembly structures, a one-step method is used to realize the construction of bismuth oxygen clusters composited with methacrylate monomers. The clusters have a bamboo-like nanomorphology and a bamboo-like structure, with a length of 80 to 200 nm and a width of about 40 nm. The specific size can be adjusted by adjusting the reaction parameters. The nanoclusters show obvious toxicity after being internalized by bladder cancer cells, and achieve efficient inhibition of bladder cancer cell proliferation under X-ray irradiation. The present invention reports for the first time bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure, and explores the regulation mode of the nanostructure in terms of mechanism. At the same time, it provides a potential nanoformulation for the treatment of bladder cancer, with extremely high nanomaterial construction and clinical diagnosis and treatment benefits.
[0045] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing bismuth oxygen methacrylate hybrid nanoclusters with bamboo-like structures, characterized in that: The following steps are involved: S1, dissolving a bismuth-containing compound in an organic solvent at a certain temperature to form a bismuth-containing organic solution; S2. Adding sodium methacrylate to the bismuth-containing organic solution and reacting it at a certain temperature for a period of time; collecting the reaction product from the reaction solution to obtain bismuth-oxygen organic hybrid nanoclusters with a bamboo-like structure.
2. The method for preparing bismuth oxygen methacrylate hybrid nanoclusters having a bamboo-like structure according to claim 1, characterized in that: In step S1, the bismuth-containing compound includes one or more of bismuth nitrate, bismuth chloride, and bismuth acetate.
3. The method for preparing bismuth oxygen methacrylate hybrid nanoclusters having a bamboo-like structure according to claim 1, characterized in that: In step S1, the concentration of the bismuth-containing compound in the bismuth-containing organic solution is 0.06-0.03 g / mL; And / or, in step S1, the organic solvent includes one or more of dimethyl sulfoxide, tetrahydrofuran, ethyl acetate, diethyl ether, and N,N-dimethylformamide. And / or, in step S1, the temperature condition is 70-90 o C.
4. The method for preparing bismuth oxygen methacrylate hybrid nanoclusters having a bamboo-like structure according to claim 1, characterized in that: The mass ratio of the bismuth-containing compound to sodium methacrylate is 1.5:1-3:
1.
5. The method for preparing bismuth oxygen methacrylate hybrid nanoclusters having a bamboo-like structure according to claim 1, characterized in that: In step S2, the step of collecting the reaction product from the reaction solution is to centrifuge the reaction solution, collect the precipitate, wash, centrifuge and dry to obtain the bismuth-oxygen organic hybrid nanoclusters with a bamboo-like structure.
6. The method for preparing bismuth oxygen methacrylate hybrid nanoclusters having a bamboo-like structure according to claim 5, characterized in that: In step S2, the reaction temperature is 70-90°C and the reaction time is 10-12 hours; And / or, in step S2, centrifugation conditions: 10,000-12000 rpm, 5-10 minutes.
7. A bismuth-oxygen-methacrylic acid hybrid nanocluster having a bamboo-like structure obtained by the preparation method according to any one of claims 1 to 6.
8. A method for preparing a polymer-modified bismuth-oxygen-methacrylic acid hybrid nanocluster material having a bamboo-like structure, characterized in that: The method comprises the following steps: dispersing the bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure obtained by the preparation method of any one of claims 1 to 6 or the bismuth oxygen methacrylate hybrid nanoclusters with a bamboo-like structure according to claim 7 in an organic solvent A to form a dispersion A, adding a phospholipid compound solution to the dispersion A and then ultrasonicating for a period of time; Centrifuge, collect the material deposited at the bottom of the centrifuge tube, wash, and redisperse in solvent B to form dispersion B; add polymer hydrophilic modified material to dispersion B, stir for a period of time, and obtain polymer hydrophilic modified bismuth oxygen organic hybrid nanocluster material with bamboo-like structure after the solvent evaporates.
9. The preparation method according to claim 8, characterized in that: In dispersion A, the concentration of bismuth-oxygen organic hybrid nanoclusters with bamboo-like structures is 10-20 mg / mL; and / or, the phospholipid compound comprises 1,2-dioleoyl-sn-glycero-3-phosphate sodium salt (DOPA); And / or, the polymer hydrophilic modified substance includes one or more of distearoylphosphatidylethanolamine-methoxy polyethylene glycol 5000 (DSPE-mPEG5000), methoxy polyethylene glycol 2000 derivative (mPEG2000), chitosan, and polydopamine.
10. A polymer-modified bismuth-oxygen-methacrylic acid hybrid nanocluster material having a bamboo-like structure obtained by the preparation method according to claim 8 or 9.
Citation Information
Patent Citations
Bismuth-based metal organic framework nano-material, preparation method thereof and application of bismuth-based metal organic framework nano-material in tumor photoacoustic diagnosis
CN117209791A
Use of bismuth-polymer complex in digestive tract visualization
WO2024022447A1
Cited By
Hydroxyl radical and singlet oxygen self-release type bismuth-based nanoparticle material
CN119896646A